Odor-Pollution From Fungicides Disrupts Learning and Recognition of a Common Floral Scent in Bumblebees (Bombus impatiens) - David, Natalie F.; Henry, Timothy J.; Sprayberry, Jordanna D. H. (Frontiers in Ecology and Evolution, 2022)
Background and Aims: Bumblebees provide vital pollination services to both natural and agricultural ecosystems. Consequently their declines in species-diversity and population size over the last five decades is alarming. Direct contributors to these declines include pesticides, habitat loss, and disease. However, given that colony fitness is linked to foraging success, successful conservation requires mitigation of any anthropogenic practices that negatively impact foraging. Previous work has shown that agrochemical odor-pollution, including that of fungicides, can modulate bumblebee foraging behavior. This study investigates how odor pollution from three common fungicides (Safer® Brand Garden Fungicide II, Scotts® Lawn Fungus Control, and Reliant® Systemic Fungicide) affects Bombus impatiens’ floral-odor learning and recognition using an associative learning paradigm. Methods: The effects of fungicide-odor pollution were tested in three ways: 1. Background pollution during floral-odor learning; 2. Background pollution during floral-odor recognition; and 3. Point pollution during floral-odor recognition. EAG recordings from B. impatiens confirmed the salience of all odor-stimuli and examined impacts of background fungicide-odor on antennal responses to floral-odor. To better understand how fungicide-odor structure related to behavioral data, scents were sampled (Solid Phase Microextraction) and analyzed using Gas Chromatography-Mass Spectrometry. Odors were then characterized using the Compounds Without Borders (CWB) vectorization method. Conclusions: All fungicides tested disrupted floral-odor learning and recognition for at least one concentration tested, and Scotts® was universally disruptive at all tested concentrations. All fungicides induced EAG responses, indicating they provide perceivable odor stimuli. Interestingly, two of three tested fungicides (Scotts® and Reliant®) inhibit antennal responses to Monarda fistulosa odor. Odor characterization supports previous findings that sulfurous scents could be disruptive to odor-driven foraging behaviors. Inability for foraging bumblebees to associate to rewarding floral odors in the presence of fungicidal odor pollution could have negative large-scale implications for colony health and reproductive fitness.